A framework of remote diabetic monitoring system for developing countries - Ayu, Media Anugerah; Ahmad, Barroon Isma’eel (2013)
Diabetes Mellitus or simply diabetes is a chronic metabolic disease that affects about 5% of the world population. The increasing rate of diabetes patients is a serious challenge that needs to be controlled worldwide. Management of diabetes involves monitoring blood sugar level to make sure it does not go beyond the normal range. Failure to monitor the level of glucose in diabetes patients can increase the risk of complications like hypertension, stroke, kidney disease, heart disease, skin, foot, and eye complications, etc. However, healthcare delivery cost can be reduced by using telemedicine applications that focus on monitoring patients from outside the clinics or hospitals. This paper proposes a framework of a low-cost telemedicine system based on GPRS, SMS and NFC technologies, for remote monitoring patients with diabetes. The solution presented in this paper is especially useful for developing ountries, where Internet data connection may not be available everywhere, even though GSM network can be found in almost every place. Another advantage of this system is patients with basic phone (no Internet capability) can also benefit from it, by using SMS as an alternative means of sending data to healthcare centre. Finally, we envisage the decrease in the cost of monitoring diabetes patients when this system is developed and implemented.